A long-term sampling study of copepods across a tropical creek in Mombasa, Kenya. - Okemwa, E.N. (East African Agriculture and Forestry Journal, 1992)
Surface Copepod samples were taken across Port Kilindini (Likoni Ferry), Mombasa, during April, June, August, October, December 1985 and February 1986, including six 24-h series and analysed for relative abundance. Changes were observed among abundant species of copepods, namely Corycaeus, Acrocalanus, Oithona, Acartia, Oncaea, Centropages, and Temora spp., and Macrosetella gracilis. A regular, predictable cycle caused by the spring-neap tidal and high-low tidal cylce was revealed. The night/day differences were a striking feature which was evident from the samples. Includes species that are new records in the West Indian Ocean